Digital qualitative research in sport and physical activity - Bundon, Andrea (Qualitative research in sport and physical activity, 2018)
Twitter, Facebook, online forums, blogs and websites - scholars are increasingly turning to digital sources to study sport and physical activity. This book critically examines the opportunities open to qualitative researchers working in digital spaces and offers novel insights into how the rise of new technology is helping to shape sport studies. Showcasing original research on emerging themes, trends and issues such as digital sociology, media citizenship, online gaming, Big Data, fitness apps and online fan cultures, this collection leads the way in this fast-developing field of study.